Protection by Ankle Brace for Lower-Extremity Joints in Half-Squat Parachuting Landing With a Backpack - Jiang, Tianyun; Tian, Shan; Chen, Tianhong; Fan, Xingyu; Yao, Jie; Wang, Lizhen (Frontiers in Bioengineering and Biotechnology, 2021)
Half-squat parachuting landing was a kind of activities with high impact force. Injuries on lower-extremity joints were common in half-squat parachuting landing, and would be increased with a backpack. Ankle brace was used to prevent ankle injuries in landing. However, few quantitative studies were reported about protection of an ankle brace for lower-extremity joints in half-squat parachuting landing with a backpack. This study focused on evaluating protective effects of an ankle brace in half-squat parachuting landing with a backpack. Seven male participants landed from 120 cm with a backpack and an ankle brace. Each participant performed three landing trials on every experimental condition. Kinetics and kinematics of hip, knee and ankle were analyzed. It was found that the ankle brace did not significantly affect the ground reaction force with backpack but increased the ground reaction force from 14.7±2.0 bodyweight to 16.2±1.9 bodyweight (p=0.017) without the backpack. The ankle brace significantly (p<0.05) decreased the angular displacement, angular velocity and angular acceleration of ankle both without and with the backpack. In conclusion, the ankle brace could restrict ankle motion and significantly increase ground reaction force without the backpack. However, the ankle brace did not significantly influence ground reaction force and still restrict ankle motion with the backpack. Therefore, the ankle brace was more effective in half-squat parachuting landing with the backpack than no backpack landing.